Pengaruh Beban Kerja Dan Pengembangan Karir Terhadap Kepuasan Kerja Karyawan Pada PT. Bakti Nugraha Yuda Energy Kabupaten Ogan Komering Ulu - Maulana Hadi Kusuma; Fandira Giffary (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2023)
This study discusses the Effect of Workload and Career Development on Employee Job Satisfaction at PT. Bakti Nugraha Yuda Energy Ogan Komering Ulu Regency. The population in this study were 166 respondents, and the samples taken in this study were 63 respondents. The data collection technique used in this study was through questionnaires. The analytical method used is a quantitative method using multiple linear regression tools. The results of the analysis in this study explain that the tcount of each variable Workload (X1) is 2.251, and Career Development (X2) is 2.709 which is greater than the ttable value of 2.001 which states that each variable has a partial effect on employee job satisfaction at PT. Bakti Nugraha Yuda Energy Ogan Komering Ulu Regency. Simultaneously there is the influence of Workload and Career Development on Employee Job Satisfaction at PT.Bakti Nugraha Yuda Energy. with Fcount of 20.750 greater than Ftable of 3.15, the value of the coefficient of determination (R square) of 0.409 means that in this case the contribution of Motivation and Job Satisfaction is 40.9% while the remaining 59.1% is influenced by other variables not examined in this study. This research is compensation and work performance Keywords: Workload, Career Development, Job Satisfaction